Heterologous expression, purification and biochemical characterization of a new xylanase from Myceliophthora heterothallica F.2.1.4 - de Amo, Gabriela Salvador [UNESP] (2019)
Myceliophthora heterothallica is a thermophilic fungus potentially relevant for the production of enzymes involved in the degradation of plant biomass. A xylanase encoding gene of this species was identified by means of RT-PCR using primers designed based on a xylanase coding sequence (GH11) of the fungus M. thermophila. The obtained gene was ligated to the vector pET28a(+) and the construct was transformed into Escherichia coli cells. The recombinant xylanase (r-ec-XylMh) was heterologously expressed, and the highest activity was observed at 55 °C and pH 6. The enzyme stability was greater than 70% between pH 4.5 and 9.5 and the inclusion of glycerol (50%) resulted in a significant increase in thermostability. Under these conditions, the enzyme retained more than 50% residual activity when incubated at 65 °C for 1 h, and approximately 30% activity when incubated at 70 °C for the same period. The tested cations did not increase xylanolytic activity, and the enzyme indicated significant tolerance to several phenolic compounds after 24 h, as well as high specificity for xylan, with no activity for other substrates such as CMC (carboxymethylcellulose), Avicel, pNPX (p-nitrophenyl-β-D-xylopyranoside) and pNPA (p-nitrophenyl-α-L-arabinofuranoside), and is thus, of potential relevance in pulp bleaching.